Electophysiological assessments of the effects of Glycemic events, Ascorbic acid and Thaimine, on the Peripheral Neuropathy of Diabetes Mellitus Patients - I.W.M. Al- Hasan; G.A. Al- Sharify (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Three groups of patients who had diabetes mellitus for 10 years were enrolled in the study and compared with the control group. Electrophysiological study on seven peripheral nerves were carried out once in the control subjects and four times in the diabetic patients; the first examination was conducted prior to drug supplement and the subsequent reexaminations conducted at the end of 6; 12 and 18 months following the drugs treatments, ascorbic acid (AA) and Thiamine (B1). The results indicate that improvements in latency, velocity and amplitude of the nerves evoked responses were significantly better with the use of AA compared to thiamine use in the patients. The results also show that the improvements were significantly greater in insulin dependent diabetes mellitus (IDDM) compared to that of non insulin dependent diabetes mellitus (NIDDM) patients with the presence of AA in both groups.Nevertheless the results indicate that with better glycemic control, the tested nerves show variable degrees of functional improvements detected by the three examined parameters at the end of the 6 and 12 months. At the end of the last visit (18 months after the first visit) more improvements were observed in the three parameters of IDDM patients. Key words: Ascorbic acid, Thiamine, Insulin, effectiveness, Diabetic Neuropathy.